ØªØ·ÙˆÙŠØ± Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ù„Ù…Ø§Ø¯Ø© Ø§Ù„Ù†ØÙˆ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø¨Ø±Ù†Ø§Ù…Ø¬ Ø£Ù†Ø¯Ø±ÙˆÙŠØ¯ Ù„Ø¯ÙŠ Ø·Ù„Ø¨Ø© Ù‚Ø³Ù… ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø¬Ø§Ù…Ø¹Ø© ÙŠÙˆØ¯Ø§Ø±ØªØ§ Ø¨Ø§Ø³ÙˆØ±ÙˆØ§Ù† - Muhammad Sholeh Bahruddin (Universitas Yudharta Pasuruan, 2019)
This essay discuss about syntax learning using media learning with Android aplication. The research is applied in Arabic language learning department Yudharta University of Pasuruan. Although the majority of students in the department in a boarding school environment so that it is possible to master the Arabic language students already syntax let alone science. However, the majority of students feel that syntax difficult and complex. The majority of students found the problems in syntax learning is not the media syntax learning interesting. And because of this, the researchers tried to provide a solution to the problem of teaching media proficiency level by designing an attractive and appropriate to the needs of students, the using Android aplication of teaching media was focused on teaching syntax. Based on the research objectives, the type of research used in this research is descriptive analysis using methods of research and development (R & D). The study population in this research were all students of the second semester of the Arabic learning department Yudharta University of Pasuruan academic year 2015-2016 a total of 8 students. The results of the test prior to use Android application of media syntax learning with reading comprehension is 60%, This indicates that the test results syntax understanding them low. Syntax understanding test results after using Android aplication based media learning is 73,8%, with the percentage differences 13%, this indicates that their ability in mastering high syntax. Based with the value as it has been presented that the effective learning media developed for use in syntax learning the students of Arabic language department Yudharta University of Pasuruan.